The Spl Serine Proteases Modulate Staphylococcus aureus Protein Production and Virulence in a Rabbit Model of Pneumonia - Alexandra E. Paharik (American Society for Microbiology, 2016)
ABSTRACT The Spl proteases are a group of six serine proteases that are encoded on the νSaβ pathogenicity island and are unique to Staphylococcus aureus. Despite their interesting biochemistry, their biological substrates and functions in virulence have been difficult to elucidate. We found that an spl operon mutant of the community-associated methicillin-resistant S. aureus USA300 strain LAC induced localized lung damage in a rabbit model of pneumonia, characterized by bronchopneumonia observed histologically. Disease in the mutant-infected rabbits was restricted in distribution compared to that in wild-type USA300-infected rabbits. We also found that SplA is able to cleave the mucin 16 glycoprotein from the surface of the CalU-3 lung cell line, suggesting a possible mechanism for wild-type USA300 spreading pneumonia to both lungs. Investigation of the secreted and surface proteomes of wild-type USA300 and the spl mutant revealed multiple alterations in metabolic proteins and virulence factors. This study demonstrates that the Spls modulate S. aureus physiology and virulence, identifies a human target of SplA, and suggests potential S. aureus targets of the Spl proteases. IMPORTANCE Staphylococcus aureus is a versatile human pathogen that produces an array of virulence factors, including several proteases. Of these, six proteases called the Spls are the least characterized. Previous evidence suggests that the Spls are expressed during human infection; however, their function is unknown. Our study shows that the Spls are required for S. aureus to cause disseminated lung damage during pneumonia. Further, we present the first example of a human protein cut by an Spl protease. Although the Spls were predicted not to cut staphylococcal proteins, we also show that an spl mutant has altered abundance of both secreted and surface-associated proteins. This work provides novel insight into the function of Spls during infection and their potential ability to degrade both staphylococcal and human proteins.